2013
DOI: 10.1111/codi.12159
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of positron emission tomography/computed tomography‐positive inguinal nodes in rectal cancer after neoadjuvant chemoradiation

Abstract: Uptake of inguinal nodes at PET/CT may be present in up to 17% of patients with distal rectal cancer, particularly with ultra-low tumours. Nearly half of these nodes no longer show uptake after CRT despite the groin area not being included in the radiation field. Persistence of inguinal node uptake 12 weeks after CRT completion may be a marker for worse oncological outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…After RCT, inguinal lymph nodes were seen in a few patients as reported before [ 31 ], These findings could be found either unilaterally or bilaterally. Most interestingly, the same inguinal lymph nodes could be seen in F-18 FDG and F-18 FLT PET/CT in 3 patients.…”
Section: Discussionsupporting
confidence: 71%
“…After RCT, inguinal lymph nodes were seen in a few patients as reported before [ 31 ], These findings could be found either unilaterally or bilaterally. Most interestingly, the same inguinal lymph nodes could be seen in F-18 FDG and F-18 FLT PET/CT in 3 patients.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, identification of the disease characteristics linked to an increased risk of developing IGN recurrence in addition to ACI will assist in decisions regarding elective IGN irradiation in the minority of patients who will benefit from this treatment despite the potential for complications. Research in rectal cancer has included the sentinel node procedure [ 21 ], serial acquisition of 18 F-deoxyfluoroglucose positron emission tomography-CT [ 22 ], and the study of histological tumor features at the distal front invading the dentate line [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, PET-CT findings compared with clinical and pathologic findings and resulted in a sensitivity of 93%, specificity of 53%, a negative predictive value of 73%, a positive predictive value of 87%, and an overall accuracy of 85% for the detection of persistent residual cancer (i.e. an incomplete response) 41. They concluded that the combination of clinical and PET-CT findings provide a safe and appropriate selection of patients who may attain a cCR after neoadjuvant chemotherapy.…”
Section: Pet-ctmentioning
confidence: 99%
“…This can be potentially expanded to predicting tumor response following CRT. In 2013, Perez and colleagues reported their results of a prospective randomized trial in which PET-CT is used to evaluate the inguinal nodes in patients who received neoadjuvant chemoradiation therapy for low rectal cancer 41. Patients were assessed for tumor response at 12 weeks after the completion of CRT by a single colorectal surgeon who used clinical and endoscopic approaches identical to those used at the initial assessment.…”
Section: Pet-ctmentioning
confidence: 99%